Solving e^x=ln(x)/log(x)

preview_player
Показать описание
If you need to post a picture of your solution or idea:
#ChallengingMathProblems #ExponentialEquations

PLAYLISTS 🎵 :

Рекомендации по теме
Комментарии
Автор

Before watching the video:
Given:
e↑x = ln(x)/log(x)

Clearly here x cannot be 1 to ensure RHS is defined, so:
log(x)·(e↑x) = ln(x)

Using change-of-base:
ln(x)·(e↑x)/ln(10) = ln(x)

Moving all terms to LHS:
ln(x)·(e↑x)/ln(10) – ln(x) = 0
ln(x)·(e↑x/ln(10) – 1) = 0

But as ln(x) cannot be 0:
(e↑x)/ln(10) – 1 = 0
e↑x/ln(10) = 1
e↑x = ln(10)

Taking natural log on both sides:
x = ln(ln(10)).

GirishManjunathMusic
Автор

One of the few times where the 1st method is easier than the second one

Anmol_Sinha
Автор

swap bases with input
use property(log x/log y = log base y input x)
U will end up with e^x= ln 10
Take natural log once and ur done
x=ln(ln(10))

TechyMage
Автор

Hey, hope you are having a nice day :)
So basically, we were taught that
lnx= 2.303 x logx.
So if we substitute ln x in the equation,
We get e^x = 2.303...
By logging
x=ln(2.303)
Which is exactly ln(ln10).
The value is like x= 0.834, a constant
Which satisfies the equation e^x=2.303.

konoveldorada
Автор

Nice problem! I did method #1. Since e^x is on the left side of the equation, it makes sense to use change-of-base to change everything on the right to natural logs. If you remember that log(x) has an implied base of 10 if none is shown, converting it and simplifying the expression is very easy.

Skank_and_Gutterboy
Автор

شكرا عله جهودكم واتمنى لكم مع اقتراب عيد اضحى مبارك ان يسعدكم

sabrenhatam
Автор

This equation e^x=ln(x)/log(x) can be written using the change of base of formula as e^x=ln(x)ln(10)/ln(x). Notice that ln(x) cancels each other out leaving the equation as e^x=ln(10), which means that x=ln(ln(10)).

justabunga
Автор

I love this guy’s occasional humor and puns throughout the video. Makes me giggle sometimes

OCEAN-fcwl
Автор

Good video Syber, in method 2 however when using the substitution you forgot to substitute 10^u for x in e^x. It should look like the following, ln(e^10^u) =ln(ln(10))= 10^u= 10^log(x)=x.

moeberry
Автор

lnx/logx = lnx/(lnx/ln10) = ln10

So we have e^x = ln10, thus
x = ln(ln10)

seanfraser
Автор

Nice video as always.
The graph of ln x/log x can be a bit misleading. It is defined for x>0 where x≠1. It's easy to miss the hole in the graph at x=1.

MichaelRothwell
Автор

Bhai maine 10 sec. Me kar diya

Sach me

Yakeen nhi ho rha
Anyways it was easier
😁

chandrashekharmehta
Автор

e^x = lnx / (lnx / ln 10)
e^x = ln 10
x = ln (ln 10)

mryip
Автор

I'm watching your videos for a couple of months. You constantly trying to assume that LogX is on base 10. You don't have to assume 🙂
In many countries this has a specific expression: LogX on base 10 is LgX. Again, it's written as LgX - equivalent of LogX on base 10.
LgX 🙂
Thanks

borisfishgal
Автор

Hmm, I used the identity twice, but I must have done something wrong. ln(x)/log(x) = log(e). If e^x = log(e), then x = ln(log(e)). But it is incorrect, because x<0. :-( So it's not in the domain...

snejpu
Автор

Cool but ur videos would be much better if u wrote on a white page and stopped coloring the equations with such extreme colors.

ethanthiebaut